A sequence { a n } satisfies the below recurrence relation for all natural numbers n :
⎩ ⎪ ⎨ ⎪ ⎧ a 1 = 3 2 , a 2 = 2 4 ; a n + 2 = a n + 1 1 3 ⋅ a n 3 7 .
Find the value of 1 0 0 0 ( 1 0 0 0 a 2 0 1 7 − ⌊ 1 0 0 0 a 2 0 1 7 ⌋ ) .
Notation: ⌊ ⋅ ⌋ denotes the floor function .
This problem is a part of <Christmas Streak 2017> series .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The first line is missing a negative sign, right? It's always true that ⌊ x ⌋ − x is negative (or zero), so the answer as written should be − 3 2 , no?
Log in to reply
Oh right, sorry, I'll edit the question. Thank you!
Problem Loading...
Note Loading...
Set Loading...
Firstly before we start anything, 1 0 0 0 a 2 0 1 7 − ⌊ 1 0 0 0 a 2 0 1 7 ⌋ expresses the fractional part of 1 0 0 0 a 2 0 1 7 .
And cause a 2 0 1 7 is a natural number, we see that what we're trying to get is the remainder when a 2 0 1 7 is divided by 1 0 0 0 .
Since a 1 is already divisible by 8 , we can all know that a 2 0 1 7 ≡ 0 ( m o d 8 ) .
Then all we need to know is the remainder of a 2 0 1 7 when it's divided by 1 2 5 .
Let 2 b n ≡ a n ( m o d 1 2 5 ) , and then we see that a 1 = 2 5 and a 2 ≡ 2 1 0 ( m o d 1 2 5 ) .
Therefore we can set b 1 = 5 , b 2 = 1 0 , b n + 2 = 1 3 b n + 1 + 3 7 b n .
Since 2 1 0 0 = 2 ϕ ( 1 2 5 ) ≡ 1 ( m o d 1 2 5 ) , we can see that all we need is the remainder when b 2 0 1 7 is divided by 1 0 0 .
Let's study about b 2 0 1 7 with mod 4 and mod 25 then.
b n + 2 = b n + 1 + b n ( m o d 4 ) , and since
( b 1 , b 2 , b 3 , b 4 , b 5 , b 6 , b 7 , b 8 , b 9 , ⋯ ) = ( 1 , 2 , 3 , 1 , 0 , 1 , 1 , 2 , 3 , ⋯ ) , we can see that b n + 6 ≡ b n ( m o d 4 ) .
Therefore b 2 0 1 7 ≡ b 1 = 1 ( m o d 4 ) .
We all know that b n is always divisible by 5 , since b 1 ≡ b 2 ≡ 0 ( m o d 5 ) .
So we'll set b n = 5 c n , and all we need is the remainder when c 2 0 1 7 is divided by 5 .
c n + 2 ≡ 3 c n + 1 + 2 c n ( m o d 5 ) .
( c 1 , c 2 , c 3 , c 4 , ⋯ , c 2 3 , c 2 4 , c 2 5 , ⋯ ) = ( 1 , 2 , 3 , 3 , 0 , 1 , 3 , 1 , 4 , 4 , 0 , 3 , 4 , 3 , 2 , 2 , 0 , 4 , 2 , 4 , 1 , 1 , 0 , 2 , 1 , 2 , 3 , ⋯ ) ( m o d 5 ) .
Therefore c n + 2 4 ≡ c n ( m o d 5 ) , and c 2 0 1 7 ≡ c 1 = 1 ( m o d 5 ) .
And so b 2 0 1 7 ≡ 5 ( m o d 2 5 ) .
From above we see that b 2 0 1 7 ≡ 5 ( m o d 1 0 0 ) , by the Chinese Remainder Theorem .
Then a 2 0 1 7 ≡ 2 b 2 0 1 7 ≡ 3 2 ( m o d 1 2 5 ) .
Therefore, using the Chinese Remainder Theorem again, we get a 2 0 1 7 ≡ 3 2 ( m o d 1 0 0 0 ) .